Exploring Opportunities and Challenges of Destination Branding of Pokhara - Malla, Subash (Journal of Interdisciplinary Studies, 2024)
The tourism industry is one of the fastest growing industry and has been a key factor for economic growth in several developing countries. But in the present era of globalization, due to rapid technological changes and increased global competition, destinations are now also directed towards branding themselves to deliver the correct brand image in the global arena. Pokhara has been the pioneer tourism destination and the market leader destination in Nepal. Due to the unique and stunning view of mountains, lakes and other natural, cultural as well as cultural amenities, Pokhara has been the first choice of tourists coming to Nepal and so it has been living with its self-made destination brand. This research has been carried on the same background to find the real essence of destination branding in an exploratory approach using In-depth Interview as the methodology of data collection. The opportunities and challenges of destination branding of Pokhara have been discussed using the various determinants. 5 experts were taken as the key informants from diverse fields in order to get the valid and reliable data. The research has provided with some framework of destination branding of Pokhara under the brand name ‘Paradise Pokhara’ and tagline/slogan ‘Nature, Culture and Adventure’.